Nanometer Titanium Dioxide Mediated High Efficiency Photodegradation of Fluazifop-p-Butyl - Guangling Li (International Journal of Environmental Research and Public Health, 2019)
The widespread use of fluazifop-p-butyl (FPB) contributes to its presence in the environment. Considering the ecological risks of FPB residues in the environment, the anatase nanometer titanium dioxide (nano-TiO2) mediated photocatalytic degradation of FPB was studied by smearing FPB and nano-TiO2 together on a glass plane; illumination, trimethylsilane derivatization of photolysis products, high performance liquid chromatography (HPLC) quantitative analysis and gas chromatograph-mass spectrometer (GC-MS) identification were used. Results showed that the first order dynamic model could describe the photodegradation of FPB by nano-TiO2 mediated, and the photodegradation and photosensitization rates were found to be positively correlated with the dose of nano-TiO2 at lower dose ranges. It is noticeable that a strong photosensitization effect was exhibited on degradation of FPB, not only under high-pressure mercury lamps, but also simulated sunlight (xenon lamp light). Ultimately, twelve main photolytic products were reasonably speculated, whilst five photolysis pathways were proposed. These results together suggest that nano-TiO2 can be used as an effective photosensitizer to accelerate FPB photolysis.